Pyramidal system involvement in progressive supranuclear palsy - a clinicopathological correlation - Stejskalova, Zuzana; Rohan, Zdenek; Rusina, Robert; Tesar, Adam; Kukal, Jaromir; Kovacs, Gabor G; Bartos, Ales; Matej, Radoslav (BMC neurology, 2019)
BACKGROUND: We aimed to produce a detailed neuropathological analysis of pyramidal motor system pathology and provide its clinical pathological correlation in cases with definite progressive supranuclear palsy (PSP). METHODS: Pyramidal motor system pathologies were analyzed in 18 cases with neuropathologically confirmed PSP. Based on a retrospective clinical analysis, cases were subtyped according to Movement Disorder Society criteria for clinical diagnosis of PSP as probable, possible or suggestive of PSP with Richardson's syndrome (n = 10), PSP with predominant corticobasal syndrome (n = 3), PSP with predominant parkinsonism (n = 3), PSP with predominant speech/language disorder (n = 1), and PSP with progressive gait freezing (n = 1). Clinical manifestations of motor neuron involvement (pseudobulbar or bulbar signs and spasticity) were retrospectively assessed semiquantitatively. Neuropathologically, hyperphosphorylated tau-related pyramidal motor system neuronal, neuritic, and glial pathology using anti-tau AT8 clone immunohistochemistry, was also evaluated. RESULTS: Clinical manifestations of pyramidal motor system involvement were found in patients with different PSP subtypes. A statistically significant higher load of tau pathology was found in the pyramidal system in PSP-Richardson's syndrome compared to other PSP subtypes (p = 0.016); however, there was no significant correlation between pyramidal system tau pathology and related motor clinical symptoms. CONCLUSIONS: Tau pathology in the spinal cord and pyramidal motor system structures is very common in progressive supranuclear palsy and may neuropathologically supplement the distinction between classic Richardson's syndrome from other progressive supranuclear palsy subtypes.
Keywords: senioři nad 80 let; parkinsonské poruchy; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Parkinsonian Disorders; Pyramidal Tracts; Cerebral Cortex; imunohistochemie; proteiny tau; mužské pohlaví; Immunohistochemistry; Supranuclear Palsy, Progressive; mozková kůra; pohybové poruchy; pyramidové dráhy; ženské pohlaví; progresivní supranukleární obrna; tau Proteins; Movement Disorders; lidé; Aged; senioři; Male; Retrospective Studies; Female